Enabling fast charging of lithium-ion batteries through secondary-/dual- pore network: Part II - numerical model. (1st May 2020) - Mai, Weijie; Usseglio-Viretta, Francois L.E.; Colclasure, Andrew M.; Smith, Kandler
Abstract: To increase the market share of electric vehicles, it is desirable to reduce the battery charge times, which are significantly limited by poor electrolyte transport. A high rate charging is achievable by using expensive and low energy density cells with thin electrodes. For higher energy density cells, new electrolytes with improved conductivity and diffusivity and/or electrodes with advanced architecture are required to boost the electrolyte transport, leading to a more uniform utilization of active materials. In our previous work, an analytical model was developed to investigate the effect of secondary pore network (SPN) on electrolyte transport and the configuration of SPN was optimized by enforcing equal characteristic diffusion times in through-plane and in-plane directions. To evaluate the effect of SPN on the fast-charging capability of lithium-ion batteries, a 2D physics-based electrochemical model is developed with SPN in either one or both electrodes. The effect of SPN on cell energy density and lithium plating is investigated for cells with different loadings and electrode porosities. Combining SPN with elevated charging temperatures, the model predicts that the volumetric discharge energy density of a 3 mA h/cm 2 cell can reach 270 Wh/L after a 6C constant-current charging. Highlights: SPN could adversely affect fast charging capability if poorly designed. Optimal SPN architecture requires narrow primary and secondary regions. SPN is more effective for cells with intermediate loading and electrode porosity.